Physician Wages in States with Expanded APRN Scope of Practice - Patricia Pittman; Benjamin Williams (Nursing Research and Practice)
In recent years, states have looked to reforms in advanced practice nursing scope of practice (SOP) barriers as a potential means to increase access to primary care while reducing costs. Currently, 16 states and the District of Columbia permit advanced practice registered nurses to practice independently of physicians, allowing them to perform functions such as diagnosing and prescribing under their own authority within the primary care setting. Given the resistance of many physician associations to these reforms, we asked whether the economic interests of primary care physicians might be affected by reforms. Using the Bureau of Labor Statistics data on earnings, we compared primary care physicians' earnings in states that have instituted SOP reforms to those that maintain these practice barriers. We also compared surgeons' earnings as a control group. Lastly, we compared the rate of growth in the earnings of primary care physicians and surgeons over the last ten years. This preliminary analysis revealed no evidence of differences in earnings across the two groups of states.